The presence of the black and indigenous difference in higher education and the process of brazilian university - Silva, José Bonifácio Alves da; Backes, José Licínio (Universidade Estadual de Campinas, 2016)
The article is a discussion about the strained relations of power between different cultures at the university. The academy and science become targets of questioning as they are questioned, especially by the active presence of blacks and indigenous inside while eurocentradas inventions conceived / conceive white cultures as the only sources and valid IDs for the production of knowledge and truth. We focus, first, the constituent elements of socio-cultural university and later show the impacts of the presence of blacks and indigenous people claiming spaces in universities. This presence as we will argue, reframes the university because the knowledge / power of black and indigenous groups infiltrate the hegemonic knowledge, placing the white hegemony in check.